La política archivística del Gobierno español y la ausencia de gestión del pasado desde el comienzo de la transición - González Quintana, Antonio (Hispania Nova. Revista de Historia Contemporánea, 2007)
Most of political parties represented at the Spanish Parliament agreed, after Franco’s death, not to face the recent past. From the beginning of the Spanish political transition has existed neither a policy of memory nor a real archival policy regarding that subject. The management of the records produced by D.N.S.D. (National Delegation of Documentary Services, the information agency of Franco regime in Salamanca), was only focused on improving historical researches. The archives of military courts, used for massive civilian repression in ther forties, thirty years after continue being the biggest gap in Spanish archival legislation. No measures have been adopted to provide accountability about Human Rights violations or to facilitate the spreading of compensations for victims of repression.